Simulations CAE of wood pellet machine - Macko Marek (MATEC Web of Conferences, 2019)
The work presents the problems of pellet production, and special attention is paid to the issues of pellet machine construction. A sample of CFD application, SolidWorks Flow Simulation, was used to analysis the flow and compaction of wood material. Examples of speed distributions inside the feed hopper and in the working system are presented.